Entomophagy practices, use patterns, and factors influencing perception and consumption frequency of edible insects in the Republic of Benin - Corinne Mèdéou Anagonou; Laura Estelle Yêyinou Loko; Anicet Gbeblonoudo Dassou; Joelle Toffa; Innocent Djegbe; Manzid Saliou; Alexandre Dansi (BMC, 2023)
Abstract Background Edible insects are important sources of essential nutrients and have the potential to contribute to malnutrition reduction and food security in the Republic of Benin. However, their consumption is always restricted to a limited number of sociocultural groups. To determine how the consumption of insects could be promoted as an alternative food source, this study documents the endogenous knowledge associated with edible insects and, the main factors that govern their perception and frequency consumption. Methods A survey was conducted towards 479 rural households consuming edible insects through 91 villages of Atacora, Alibori, Zou, and Plateau departments using individual interviews with a semi-structured questionnaire. The survey was focused on the inventory of edible insects and the documentation of consumers' acceptance, frequencies and motive reason of consumption, local uses, and accessibility to edible insects. Samples of edible insects were collected and preserved in 70% alcohol for taxonomic identification. Results The majority of surveyed people (79.1%) were consumers of edible insects since many years ago (29.1 ± 17.2 years). Insect species belonging to 17 genera of 7 families and 3 orders of insects were used as food, with Brachytrupes membranaceus Drury being the most widespread and consumed. Six factors affecting edible insect availability were identified with the chemical pollution as the most important. Besides their food use (63.2%), edible insects in the study area were used for several purposes. We find that ethnicity, religion, age, education level, and monthly frequency of insect consumption are the main factors influencing the local perception of edible insects. Indeed ethnic group, religion ethnicity, and market accessibility have a positive influence on edible insect consumption frequency. The Hierarchical Clustering of Principal Components has allowed us to classify the interviewees into 3 groups with different perceptions of entomophagy and their characteristics will make it possible to better orient the strategies for promoting entomophagy in the Republic of Benin. Conclusions Religion and tradition are among the main factors that influence entomophagy in Benin Republic. The development of a national strategy to promote entomophagy should take into account the recorded insect consumption motivations, and their different uses by each ethnic group, and mainly target young people.